2012
DOI: 10.1371/journal.pone.0032711
|View full text |Cite
|
Sign up to set email alerts
|

Is Opium a Real Risk Factor for Esophageal Cancer or Just a Methodological Artifact? Hospital and Neighborhood Controls in Case-Control Studies

Abstract: BackgroundControl selection is a major challenge in epidemiologic case-control studies. The aim of our study was to evaluate using hospital versus neighborhood control groups in studying risk factors of esophageal squamous cell carcinoma (ESCC).Methodology/Principal FindingsWe compared the results of two different case-control studies of ESCC conducted in the same region by a single research group. Case definition and enrollment were the same in the two studies, but control selection differed. In the first stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
44
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 37 publications
(47 citation statements)
references
References 23 publications
3
44
0
Order By: Relevance
“…Strengths of our study include enrolling biopsy-proven gastric adenocarcinoma cases and population-based controls (53) , and administration of a reliable and validated questionnaire. Our study also has some limitations.…”
Section: Discussionmentioning
confidence: 99%
“…Strengths of our study include enrolling biopsy-proven gastric adenocarcinoma cases and population-based controls (53) , and administration of a reliable and validated questionnaire. Our study also has some limitations.…”
Section: Discussionmentioning
confidence: 99%
“…Cohort participants completed general and food frequency questionnaires similar to those for cases (see below), and gave blood, hair and nail samples. We have previously shown that controls from this cohort correctly reflect opium use in the neighborhoods of cancer cases, and compared to hospital controls, they provide more accurate estimates of cancer risks due to opium or tobacco consumption 11 .…”
Section: Methodsmentioning
confidence: 86%
“…Regular use of opium has been reported to be associated with increased risk of several cancers, including esophageal cancer 9-11 , laryngeal cancer 12 , bladder cancer 13-15 , and lung cancer 16 , but to our knowledge no epidemiologic studies of opium use and gastric cancer have been published. About 0.3-0.5% of the world’s population in the 15-64 year old age group, between 12 and 21 million people, used opiates at least once in 2009 17 .…”
Section: Introductionmentioning
confidence: 96%
“…For example, cases were confirmed based on histopathological diagnosis history to prevent the misclassification bias. Also, population based neighbor control was used to control the confounding effects of socioeconomic factors, exposure to the environmental risk factors and other potential unknown confounders that may confound the associations (47). Moreover, as an advantage, the validity and reliability of the questionnaire in this study were verified for Iranian population (33).…”
Section: Discussionmentioning
confidence: 99%